Bovine Lactoferrin Enhances TLR7-Mediated Responses in Plasmacytoid Dendritic Cells in Elderly Women: Results From a Nutritional Intervention Study With Bovine Lactoferrin, GOS and Vitamin D - van Splunter, Marloes; Perdijk, Olaf; Fick-Brinkhof, Henriëtte; Feitsma, Anouk L.; Floris-Vollenbroek, Esther G.; Meijer, Ben; Brugman, Sylvia; Savelkoul, Huub F. J.; van Hoffen, Els; van Neerven, R. J. Joost (Frontiers in Immunology, 2018)
During ageing the immune system is dysregulated. Especially plasmacytoid dendritic cells (pDCs) and myeloid DCs (mDCs) have reduced Toll like receptor (TLR)-mediated responses resulting in increased susceptibility to infections. Consumption of bovine lactoferrin (bLF) has been shown to reduce infections with viruses. Galactooligosacharides (GOS) and vitamin D are associated with reduced pro-inflammatory cytokine levels in serum, and increased TLR7/8 responses, respectively. A double-blind placebo-controlled nutritional intervention study in elderly women was performed, to investigate the potential of bLF, GOS and vitamin D to restore TLR responsiveness of pDCs and mDCs and to reduce inflammatory markers in serum. The nutritional intervention group (n=15) received 3 weeks of bLF, followed by 3 weeks of bLF + GOS, and subsequently 3 weeks of bLF + GOS + vitamin D. The placebo group (n=15) received maltodextrin for 9 weeks. Every 3 weeks, blood was collected and TLR responses of pDCs and mDCs and inflammation-related markers in serum were measured. After 3 weeks of bLF supplementation, increased TLR7/8 and TLR1/2 responses were observed in pDCs of the nutritional intervention group compared to the placebo group. When the effects of the entire nutritional intervention were investigated, increased TLR1/2 mediated responses in mDCs were observed, and in serum sVCAM tended to decrease. Finally, based on the RAND-36 questionnaire physical function tended to improve in the intervention group. Since, especially TLR7-mediated responses in pDCs were enhanced after bLF supplementation compared to placebo, this suggests that bLF may contribute to antiviral responses mediated by pDC in elderly women. Clinical trial registry number: NCT03026244, clinicaltrials.gov